B.D. Graham. Hindu Nationalism and Indian Politics: The Origins and Development of the Bharatiya Jana Sangh. Nueva York: Cambridge University Press, 1990, 283 pp. - Lorenzen, David N. (Estudios de Asia y África, 1992)
-